STATISTICAL DATA ANALYSIS IN GAMMA AND X-RAY SPECTROMETRY - Safarov Abror; Mukhammedov Umidjon; Ashurov Sindorjon (Galaxy International Interdisciplinary Research Journal, 2024)
This paper presents a detailed examination of statistical data analysis methods employed in gamma (γ) and X-ray spectrometry. Emphasis is placed on the application of Gaussian distribution to model the statistical deviations in measurement data. We discuss the derivation of key parameters such as mean and standard deviation from measured quantities, and their significance in ensuring accurate results. Through practical examples and Python code for plotting histograms, the paper demonstrates how statistical analysis can be used to interpret spectrometric data, providing insights into radiation sources and measurement uncertainties.